The development of a constructionist learning model for social technologies - Parmaxi, Antigoni (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2015)
The rapid popularity of social technologies has led to a wide spread of research studies conducted in formal and informal contexts demonstrating a wide range of their benefits in teaching and learning. Yet, the burst of studies exploring these technologies confronts with two threads with regard to their theoretical and pedagogical alignment. Firstly, a substantial number of studies is not aligned to a theoretical framework; whereas the implementation of Web 2.0 technologies in classroom settings calls for better task-technology alignment. The conundrum raised is that, whilst students increasingly engage with these tools in their everyday lives, there is still lack of Web 2.0 practices that draw on the specific features of these tools and align them with educational goals under well-designed activities. With this in mind, this dissertation brought forward a three-year intervention, employing constructionism as an overarching theoretical framework, and unpacking the potential of social technologies as instructional tools that support social construction of artifacts by groups of language learners. The leading research question of this dissertation is “How can constructionism ground and expand the use of social technologies as social constructionist tools in learning?”. Constructionism is a theory of learning, teaching, and design, which can be summarized in the conviction that learning occurs more effectively when learners understand the world around them by creating meaningful artifacts that can be probed and shared. In an attempt to infuse elements of constructionism in the use of social technologies, group of learners were assigned a task for social construction of an artifact using social technologies in three different Computer-Assisted Language Learning settings To understand the use of social technologies through the lens of constructionism, the process that students adopted and the way technology and context fostered this process were analyzed. The implementation of the intervention made feasible the identification of (i) core dimensions of social technologies as social constructionist tools; (ii) actions that capitalize the manifestation of constructionism within social technologies (iii) teacher‟s and students‟ role within social constructionist tools; and (iv) features of different social technologies as social constructionist tools. The main component of this dissertation is the constructionist model that demonstrates the core dimensions of social technologies as social constructionist tools, with actions held for the social construction of an artifact; and a set of instructional design elements that encloses the theoretical understanding of the classroom whilst groups of learners use social technologies for constructing an artifact. The Social Constructionist Classroom (SCC) yields an environment rich in objects-to-share-with, following an artifact oriented task design and fostered through synergetic alliance of multiple social technologies, whilst moving beyond classroom walls. As a result, the findings of this dissertation provide an in-depth understanding of how social technologies can be used for facilitating groups of learners to socially construct a shared artifact. Moreover, through the analysis of different types of social technologies, a new arena for using social technologies is deployed, offering insights for multimedia designers, interface architects, instructional designers, and practitioners towards a new culture of educational tools.
Keywords: Social media; Social computing; Computer-assisted language learning; Technology-enhanced learning; Language learning; Artifact; Object-to-share-with; Microworlds; Social microworlds